Study Of Signal Processing Of Engine Knocking On Vehicle - Rauf, Ahmad Arifin Abd (Universiti Sains Malaysia, 2017)
An engine is a device or machine designed to convert one form of energy into another form which is from thermal energy to mechanical energy. However, while transforming energy from one form to another form, the efficiency of conversion plays an important role. From this, the air fuel ratio is the main factor where the efficiency of combustion is determined inside the engine. Engine knock has long been a well-recognized phenomenon in the automotive industry. Detecting engine knock opens up the possibility for an indirect feedback of the engine’s internal combustion without installing a pressure transducer inside the cylinder. Knock detection has mainly been used for spark advance control, making it possible to control the engine close to its knock limit in search for the optimal ignition timing. Detecting engine knock opens up the possibility for an indirect feedback of the engine’s internal combustion without installing a pressure transducer inside the cylinder. The research were done on the suitable using the knocking sensor in the exhaust stream after the combustion process. Using the standard Air/Fuel ratio of the gasoline engine, the program for controlling the fuel injection into the internal combustion engine is made using the Arduino controller. Then, the data is collected and will be analyses and also compared with other data. This thesis is submitted for the partial requirement of final year project named Study Signal Processing of Engine Knocking on Vehicle Using Closed Loop System. Gasoline and diesel engine are widely used in industry and agricultural field, and it has different performance, combustion and vibration characteristics in the internal combustion engine. This project will study based on signal processing of engine knocking for the gasoline engine. Engine knock has long been a well-recognized phenomenon in the automotive industry.